Growth of trees and microclimates in a gap dependent forest in Central Amazonia - Tsuchiya, Akio; Tanaka, Akira; Higuchi, Niro; Lisboa, Pedro Braga (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2006)
Forest inventory, stem core sampling, and meteorological observations were carried out in a dense tropical forest in Novo Aripuanã, Amazonas. In the research quadrat (1.9 ha), 210 woody species belonging to over 38 botanical families, and 14 palm species were identified. The aboveground biomass, which was estimated to be 202.72 t/ha, was standard for Amazonia, but the forest was considered to repeat regeneration by tree-fall gaps because early succession species such as Iryanthera ssp. Myristicaceae), Croton sp (Euphorbiaceae), and palms were large in number. The relationship between tree height and percentage of vessel area in stem cross sections in the 2001 and 2002 growth rings had a positive correlation coefficient. The enlargement of vessel area was to improve the efficiency for absorbing sap against gravity, which means that the increase in pore zone leads to weakening the resistance of stems against squalls. From meteorological measurements, it was found that diurnal downward short-wave radiation at forest canopy was a few times to several dozen times as large as that at forest floor, and in consequence, net radiation surpassed 600 w/m2 in the canopy, while it was about 30 w/m2 on the floor. The radiation balance in tree-fall gaps was similar to that of forest canopy, but the gaps were characterized to have a large temperature difference between day and night (12 to 13 oC). Radiative cooling easily condensed humid air when temperatures decreased to 27-28 oC, and the condensation each night amounted to 5-7 g/m3, about double that of closed forests.
Keywords: Central Amazonia; Tree-fall gap; Vessel parameters; Radiation balance; Microclimate